Comparing the Cytotoxic Effects of Clove Essential Oil (Syzygium Aromaticum) and its Major Compound (Eugenol) Against Some Human Breast Cancer Cell Lines - Hiva Alipanah; Ali Ghanbariasad; Mahmoud Osanloo (Fasa University of Medical Sciences, 2020)
Background & Objective: Breast cancer is the most common cancer among women, especially in developed countries. Because of resistance to chemotropic drugs, the development of new green drugs is crucial. Essential oils with a broad range of bioactivities such as antioxidant and anticancer activities are great resources for research and development. In this study, anticancer effects of clove (Syzygium aromaticum) essential oil as the common medicinal plant against some human breast cancer cell lines was investigated. Materials & Methods: Components of clove essential oil were identified. The anticancer effect of the essential oil and its major ingredient (eugenol) was investigated on four human breast cancer cell lines. Results: Ninety-two percent of clove essential oil was included by eugenol (65%), trans-caryophyllene (12%), eugenol acetate (10%), caryophyllene oxide (3%), and a-humulene (2%). Both clove essential oil and eugenol showed proper effect (IC50 µg.mL-1) on targeted cell lines, MCF-7 (151.94 and 86.13), MDA-MB-175 (162.92 and 33.25), MDA-MB-231 (180.61 and 69.75), and MDA-MB-468 (211.11 and 53.91). Conclusions: Regarding the proper anticancer effects of both samples, they could be considered as anticancer agents for further investigation.